Pengaruh Pemakaian Alat Pelindung Telinga (earplug) terhadap Tekanan Darah Akibat Bising (Penelitian pada Pekerja Penggilingan Padi di Kecamatan Karanganyar Kabupaten Karanganyar) - Hidayat, Samsul N; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2005)
ABSTRACT Background : Noise is the sound disliked or unwanted by anyone. In addition to its effect on hearing, noise exposure has also been implicated as having other physiological effect. Specifically, non-auditory physiological effect of noise exposure that have been identified thus far include cardiovascular effect. Probably the most attention has been directed toward cardiovascular effect, especially potential elevation in blood pressure. The aim of this study was to analyze the influence of using hearing protection devices on blood pressure regarding with noise exposure. This study was conducted on 30-male rice mill workers as the sample. That samples size were met with inclusion and exclusion criteria.This study was classified as quasi experiment with group pretest posttest design. Method : This study was devided into 2 groups of surveilence, on the 1’st group, consisted of worker who using hearing protection devices during its workshift and then  the 2’nd one consisted of the same workers but they have never used of hearing protection devices. Confounding variables were controlled, included : ages, smoking habit, obesity, work-load, family history, inactivities. Blood pressure was measured by using mercury sphygnomanomater. The measurenment of blood pressure were taken 2 times ; at the beginning of the workshift and the end of the workshift on both groups. Result : The result showed that noise intensity was beyond the threshold limit values (85 dB) on the all of rice mill industry where the study was conducted. From the statistical paired t test, it found out that there was a difference in mean of systolic and diastolic blood pressure between the workers who using earplug and workers that have never used earplug. Conclusion : Workers with earplug had lower systolic and diastolic blood pressure rather than those who didn’t use earplug, workers of using hearing protection was associated with a lower in systolic and diastolic blood pressure of 14,6 mmHg and 6,67 mmHg. Key words : Noise, earplug, blood pressure